2000
DOI: 10.1084/jem.192.11.1535
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Priming of Naive Cd8 T Cells against Melanoma Antigens Using Dendritic Cells Loaded with Killed Allogeneic Melanoma Cells

Abstract: The goal of tumor immunotherapy is to elicit immune responses against autologous tumors. It would be highly desirable that such responses include multiple T cell clones against multiple tumor antigens. This could be obtained using the antigen presenting capacity of dendritic cells (DCs) and cross-priming. That is, one could load the DC with tumor lines of any human histocompatibility leukocyte antigen (HLA) type to elicit T cell responses against the autologous tumor. In this study, we show that human DCs deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
161
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(166 citation statements)
references
References 38 publications
2
161
1
Order By: Relevance
“…In the present study we found that DCs phagocytosing apoptotic tumor cells elicit long-lived combined CD4 ϩ and CD8 ϩ immunity against the poorly immunogenic B16 melanoma. DCApo have been shown by Berard et al (22) to be able to prime naive human T cells in vitro to melanoma Ags. These findings together with our preclinical model set the stage for comparable studies in humans with DC-Apo as adjuvants for active immunization against cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we found that DCs phagocytosing apoptotic tumor cells elicit long-lived combined CD4 ϩ and CD8 ϩ immunity against the poorly immunogenic B16 melanoma. DCApo have been shown by Berard et al (22) to be able to prime naive human T cells in vitro to melanoma Ags. These findings together with our preclinical model set the stage for comparable studies in humans with DC-Apo as adjuvants for active immunization against cancer.…”
Section: Discussionmentioning
confidence: 99%
“…DCs are proving to be effective in initiating and expanding immune responses in humans (10,11), providing a rationale for their use as adjuvants for active immunization against melanoma (12)(13)(14)(15)(16). Different strategies have been developed to load DCs with tumor Ags, including MHC-restricted synthetic peptides derived from the Ag (12)(13)(14)(15)(16)(17), tumor RNA (18,19), tumor lysates (20), tumor-derived exosomes (21), and dying tumor cells (22)(23)(24)(25)(26); these have been assessed in preclinical models and, in some cases, clinical trials (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Tumor cells (dying cells or Ab-coated tumor cells) are of interest as an antigenic source, because the DCs would have the potential to present a broad range of tumor-associated Ags and on both MHC class I and II products regardless of the MHC haplotype of the patient (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…DCs loaded with protein can promote cellular immunity both in experimental animal models and humans (8)(9)(10)(11). Optimal antigen loading strategies provide epitopes presented by both MHC class I and class II leading to a diverse immune response in which many clones of cytotoxic T cells (CTLs) and CD4 + T cells are involved (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular requirements for the cross-presentation of exogenous antigens by DC were also extensively analyzed in the last few years [27][28][29][30][31][32][33][34]. Because most studies analyzing cross-presentation in human DC used apoptotic cells or vesicles as the source of antigen [35,36], mechanistic analyses are not fully conclusive. Purified proteins or peptides, however, have also been used in a few studies that provided some insights into the mechanisms required for antigen delivery, processing and presentation by human DC [15,18,19,32,37,38].…”
mentioning
confidence: 99%